Automobile body and manufacturing method of the same

JP2023167982A5Active Publication Date: 2025-02-26MAZDA MOTOR CORP +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2022079560
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2022-05-13
Publication Date
2025-02-26
Estimated Expiration
2042-05-13

AI Technical Summary

Technical Problem

Existing methods for forming automobile coatings struggle to achieve both whiteness and metallic texture, often resulting in a loss of brightness or whiteness when emphasizing one quality over the other.

Method used

A multilayer coating system comprising a colored coating film with a white pigment, a glittering coating film containing glittering materials, and a clear coating film, with specific spectral reflectance ratios and occupancy rates of glittering materials to enhance brightness and metallic texture.

Benefits of technology

The system achieves a balance between whiteness and metallic texture by enhancing brightness in highlights and maintaining a white tone in shaded areas, providing a visually appealing automobile body.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

To provide an automobile body characterized in that both whiteness and a metallic texture are attained, and a manufacturing method of the automobile body.SOLUTION: An automobile body includes a coated matter and bilayer coating film. The bilayer coating film includes a color coating film that is formed over the coated matter and contains a white pigment, a brilliant coating film that is formed over the color coating film and contains a brilliant material, and a clear coating film formed over the brilliant coating film. A luminosity L*45 based on a spectral reflectance that light I45 irradiated at an angle of 45 degrees with respect to the surface of the bilayer coating film is received at an angle of 45 degrees with respect to regularly reflected light is equal to or larger than 70 and equal to or smaller than 90. A ratio of a luminosity L*5 based on a spectral reflectance that the light I45 is received as an angle of 5 degrees with respect to the regularly reflected light to a luminosity L*15 based on a spectral reflectance that the light I45 is received at an angle of 15 degrees with respect to the regularly reflected light, L*5 / L*15, is equal to or larger than 1.2 and equal to or smaller than 2.5. An occupancy of the brilliant material relative to the surface of the bilayer coating film is equal to or larger than 10% and equal to or smaller than 30%. A granularity on the surface of the bilayer coating film is equal to or larger than 1.0 and equal to or smaller than 3.0.SELECTED DRAWING: Figure 2
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] The present invention relates to an automobile body and a method for manufacturing the same. [Background technology]

[0002] In recent years, technological advances have led to the proposal of coating films with a variety of colors and textures for automobile bodies. Among these, white coating films with a metallic luster have attracted attention. Patent Documents 1 and 2 disclose methods for forming coating films with a lustrous appearance and clear whiteness. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Japanese Patent Application Laid-Open No. 2003-245603 [Patent Document 2] Japanese Patent Application Laid-Open No. 2011-45805 Summary of the Invention [Problem to be solved by the invention]

[0004] However, even when using the methods of Patent Documents 1 and 2, it is difficult to achieve both whiteness and a metallic texture (for example, a lustrous feel). When whiteness is emphasized, the lustrous feel is easily lost. When the lustrous feel is emphasized, whiteness is easily lost, and the finish appears silver. The object of the present invention is to provide an automobile body that achieves both whiteness and a metallic texture, and a method for manufacturing the same. [Means for solving the problem]

[0005] In order to solve the above problems, the present invention provides the following aspects. [1] An automobile body having a coating object and a multi-layer coating film, The multi-layer coating film is a colored coating film formed on the substrate and containing a white pigment; a glittering coating film formed on the colored coating film and containing a glittering material; and a clear coating film formed on the glossy coating film, Light I was irradiated onto the surface of the multilayer coating film at an angle of 45 degrees. 45 The brightness L based on the spectral reflectance of light received at a 45-degree angle to the specular reflected light * 45 is between 70 and 90, Light I 45 The brightness L based on the spectral reflectance of light received at an angle of 5 degrees relative to the specular reflection light * 5 and the light I 45 The brightness L based on the spectral reflectance of light received at an angle of 15 degrees relative to the specular reflection light * Ratio to 15:L * 5 / L * 15 is between 1.2 and 2.5, The occupancy rate of the lustrous material as viewed from the surface of the multilayer coating film is 10% or more and 30% or less, An automobile body, wherein the graininess of the surface of the multi-layer paint film is 1.0 or more and 3.0 or less.

[0006] [2] The surface of the colored coating is irradiated with light from a 45-degree angle. 45 The brightness CL based on the spectral reflectance of light received at a 45-degree angle to the specular reflected light * 45 is 70 or more and 95 or less, the automobile body according to [1] above.

[0007] [3] The automobile body according to the above [1] or [2], wherein the thickness of the glittering coating film is 0.05 μm or more and 1.0 μm or less.

[0008] [4] The automobile body according to any one of the above [1] to [3], wherein the luster material includes a scaly luster pigment having a thickness of 0.05 μm or more and 0.3 μm or less.

[0009] [5] The automobile body according to any one of the above [1] to [4], wherein the luster material contains aluminum particles.

[0010] [6] The automobile body according to any one of the above [1] to [5], wherein the glittering coating film further contains titanium dioxide.

[0011] [7] A step of applying a colored coating containing a white pigment onto an object to be coated to form an uncured colored coating film; a step of applying a glitter pigment dispersion containing a glitter material onto the uncured colored coating film to form an uncured glitter coating film; a step of applying a clear coating material onto the uncured glossy coating film to form an uncured clear coating film; and a step of curing the uncured colored coating film, the uncured bright coating film, and the uncured clear coating film to obtain a multi-layer coating film, Light I was irradiated onto the surface of the multilayer coating film at an angle of 45 degrees. 45 The brightness L based on the spectral reflectance of light received at a 45-degree angle to the specular reflected light * 45 is between 70 and 90, Light I 45 The brightness L based on the spectral reflectance of light received at an angle of 15 degrees relative to the specular reflection light * 5 and the light I 45 The brightness L based on the spectral reflectance of light received at an angle of 15 degrees relative to the specular reflection light * Ratio to 15:L * 5 / L * 15 is between 1.2 and 2.5, The occupancy rate of the lustrous material as viewed from the surface of the multilayer coating film is 10% or more and 30% or less, A method for manufacturing an automobile body, wherein the graininess of the surface of the multi-layer paint film is 1.0 or more and 3.0 or less.

[0012] [8] The method for manufacturing an automobile body according to [7] above, wherein the clear coating is a two-component coating containing a hydroxyl group-containing resin and a polyisocyanate compound.

[0013] [9] The method for manufacturing an automobile body according to [7] or [8] above, wherein the solid content of the bright pigment dispersion is 0.1% by mass or more and 10.0% by mass or less. [Effects of the Invention]

[0014] According to the present invention, it is possible to provide an automobile body that combines whiteness with a metallic texture, and a method for manufacturing the same. [Brief explanation of the drawings]

[0015] [Figure 1] FIG. 10 is a diagram illustrating the light-receiving angle of the spectral reflectance. [Figure 2] 1 is a cross-sectional view schematically showing an automobile body according to one embodiment of the present invention. [Figure 3] 1 is a cross-sectional view schematically showing a glittering coating film according to one embodiment of the present invention. [Figure 4] 1 is a flowchart showing a method for manufacturing an automobile body according to an embodiment of the present invention. DETAILED DESCRIPTION OF THE INVENTION

[0016] A. Automobile body The automobile body according to this embodiment constitutes at least a part of an automobile. The automobile body comprises a substrate and a multilayer coating film. The multilayer coating film comprises a colored coating film formed on the substrate and containing a white pigment, a glittering coating film formed on the colored coating film and containing a luster material, and a clear coating film formed on the glittering coating film.

[0017] In order to achieve both whiteness and a metallic texture, the composite coating film enhances the brilliance in a narrow region of the highlights (hereinafter referred to as the super highlights) and increases the brightness in the shades. By limiting the region where the metallic texture is expressed to the super highlights, the automobile body can appear whiter in the shaded region.

[0018] That is, the flip-flop value (FF value) in the vicinity of the specularly reflected light is increased. The FF value is an index showing the change in lightness when the composite coating film is viewed from multiple directions. The larger the FF value, the greater the lightness difference. Increasing the FF value in the vicinity of the specularly reflected light, as in this embodiment, enhances the metallic texture in the ultra-highlight.

[0019] In this embodiment, the FF value in the vicinity of the specular reflection light is determined by irradiating the surface of the multilayer coating film with light I at an angle of 45 degrees (°). 45 The brightness L based on the spectral reflectance of light received at an angle of 5 degrees relative to the specular reflection light * 5 and the above light I 45 The brightness L based on the spectral reflectance of light received at an angle of 15 degrees relative to the specular reflection light * Ratio to 15:L * 5 / L * Find 15. L * 5 / L * 15 is between 1.2 and 2.5. * 5 / L * When 15 is in this range, the change in brightness in the highlights becomes large. In other words, a highly metallic texture is obtained in the extreme highlights, while the white tone becomes stronger in the shaded areas. * 5 / L * L 15 is preferably 1.30 or more, more preferably 1.35 or more. * 5 / L * 15 is preferably 2.40 or less, and more preferably 2.20 or less. The super highlight is the region from -10 degrees to 10 degrees relative to specular reflection light (angle 0 degrees).

[0020] Lightness L * 5. Above Light I 45 L calculated from the spectral reflectance of light received at an angle of 5 degrees relative to the specular reflection * a * b * Color space (CIE1976L * a * b * Lightness L in color space * Lightness L * 15 is similar to the above light I 45L calculated from the spectral reflectance of light received at an angle of 15 degrees relative to the specular reflection * a * b * Lightness L in the color system * The lightness L * 45 is similar to the above light I 45 L calculated from the spectral reflectance of light received at a 45-degree angle to the specular reflected light * a * b * Lightness L in the color system * Lightness L * 5. L * 15, L * All 45 values ​​can be 0 or greater. * The lightness L can be obtained using a variable goniochromaticity meter (for example, Gonio-Spectrophotometer GSP-1, manufactured by Murakami Color Materials Research Institute Co., Ltd.). * is the lightness L of five different samples * is the average value of

[0021] Lightness L * 5 is not particularly limited. In terms of enhancing the sense of brilliance, * 5 is preferably 120 or more, more preferably 150 or more. * 15 is not particularly limited. * 15 may be 90 or more, or 100 or more. The FF value tends to be large, so the lightness L * 15 is preferably 150 or less, and more preferably 130 or less. * 5 to Lightness L * The value obtained by subtracting 15 is, for example, 40 or more, preferably 45 or more, and more preferably 50 or more.

[0022] Figure 1 is a diagram illustrating the light receiving angle of the spectral reflectance. Light I is irradiated onto the surface of the multi-layer coating film at an angle of 45 degrees. 45 The specular reflection of light I is denoted by R0. 45 The light received at an angle of 5 degrees relative to the specularly reflected light is designated R5. 45 The light received at an angle of 15 degrees to the specularly reflected light of R 15Light I 45 The light received at a 45 degree angle to the specularly reflected light of R 45 is shown.

[0023] The multilayer coating film has a small graininess (hereinafter referred to as graininess G). The smaller the graininess G, the denser the composite coating film appears, and the more enhanced the metallic texture. The graininess is 1.0 or more and 3.0 or less. The graininess G is preferably 1.5 or more, and more preferably 1.8 or more. The graininess G is preferably 2.7 or less, and more preferably 2.3 or less.

[0024] The graininess G can be determined by imaging the composite coating film irradiated with diffused light and analyzing it with a specific image analysis algorithm. Specifically, the composite coating film is irradiated with diffused light from a light source installed inside a white-painted hemisphere. The composite coating film is imaged from its normal direction with a CCD camera and analyzed with a specific image analysis algorithm. The graininess G can be obtained using a multi-angle colorimeter (for example, BYK-mac i, manufactured by BYK-Gardner). Graininess G * is the average value of the graininess G of five different samples.

[0025] The occupancy rate of the luster material as viewed from the surface of the multilayer coating film is 10% or more and 30% or less. This allows the white pigment contained in the colored coating film to be seen without going through the luster material. This results in a higher brightness in the shade. The occupancy rate of the luster material is preferably 13% or more, more preferably 16% or more. The occupancy rate of the luster material is preferably 23% or less, more preferably 20% or less. In this embodiment, the particle feel G is kept low. Therefore, even if the occupancy rate of the luster material is reduced, the metallic texture can be enhanced.

[0026] The occupancy rate of the luminous material is the area ratio of the luminous material in the multilayer coating film when viewed from the normal direction. Specifically, the multilayer coating film is observed from its normal direction using an electron microscope. In the observation field, the area corresponding to the luminous material and other areas are binarized using image processing software. The area of ​​the observation field is set to 100%, and the area ratio of the luminous material is calculated. The magnification of the electron microscope is not particularly limited, and may be, for example, approximately 100 times to 200 times. The size of the observation field is also not particularly limited, and may be, for example, approximately 500 nm to 1000 nm in length and 1000 nm to 1500 nm in width. An industrial microscope (e.g., ECLIPSE LV150N, manufactured by Nikon Instech Co., Ltd.) is used as the electron microscope. As image processing software, for example, NIS-Elements (Nikon Corporation, comprehensive image software) or NIS-A AMEAS (Nikon Corporation, distance measurement and area calculation software) is used. The occupancy rate is the average value of the occupancy rates in five different observation fields.

[0027] In the multilayer coating film of this embodiment, the above-mentioned light I 45 The brightness L based on the spectral reflectance of light received at a 45-degree angle to the specular reflected light * 45 is between 70 and 90. This makes the multi-layer coating appear white from highlights to shades. * 45 is preferably 73 or more, and more preferably 75 or more. * 45 is preferably 87 or less, more preferably 85 or less.

[0028] In order to further improve the metallic texture, it is preferable that the glossy coating film contains a lustrous material aligned parallel to the coating film. In particular, it is preferable that 80% or more of the lustrous materials contained in the glossy coating film are aligned parallel to the surface of the multilayer coating film. "Parallel" means that the acute angle θ between the surface of the glossy coating film and the lustrous material in the cross section of the multilayer coating film is between 0 degrees and 30 degrees.

[0029] The arrangement of the sparkle material is indicated, for example, by the sparkle intensity of the multi-layer coating film. The sparkle intensity (hereinafter referred to as Si 15 The smaller the value of Si in the composite coating film, the more the luster material is aligned parallel to the luster coating film. 15 The value can be between 3.0 and 4.0. 15 When the value is within this range, it can be said that 80% or more of the number of glittering materials contained in the glittering coating film are aligned parallel to the surface of the glittering coating film. 15 The value is preferably 3.1 or more, more preferably 3.2 or more. 15 The value is preferably 3.8 or less, more preferably 3.6 or less.

[0030] Si 15 The value is calculated by irradiating light from a direction tilted 15 degrees from the normal direction of the multi-layer paint film, capturing an image from the normal direction of the multi-layer paint film, and analyzing it with a specific image analysis algorithm. The image analysis algorithm uses a histogram of brightness levels. 15 The value can be obtained using a multi-angle colorimeter (for example, BYK-mac i, manufactured by BYK-Gardner). 15 The values ​​are the Si values ​​of five different samples. 15 is the average of the values.

[0031] In particular, the arrangement of the scaly luster pigment (hereinafter referred to as "scaly luster pigment") can also be confirmed from the cross section of the multilayer coating film. The acute angle θ can be determined from the cross section of the multilayer coating film as follows. First, the cross section of the multilayer coating film is imaged using an electron microscope. The obtained cross section is placed on two-dimensional coordinates (xy coordinates) to determine the approximate straight line L0 of the surface of the luster coating film. In the same manner, the approximate straight line L1 of the surface of the scaly luster pigment is determined. The surface of the scaly luster pigment is the main surface closer to the clear coating film. The angle formed by the approximate lines L0 and L1 is the angle θ. The proportion of scaly luster pigments parallel to the luster coating film can be determined by dividing the number of scaly luster pigments that are arranged parallel to the luster coating film and that can be seen as a whole in the observation field by the number of luster pigments that can be seen as a whole in the observation field.

[0032] The magnification of the above-mentioned electron microscope observation is not particularly limited. The magnification of the electron microscope may be, for example, about 100 times or more and 200 times or less. The size of the observation field is also not particularly limited, and may be, for example, about 500 nm to 1000 nm in length and about 1000 nm to 1500 nm in width. The magnification and observation field of the following electron microscope observations may also be similar to those described above.

[0033] In the lustrous coating film, it is preferable that the scale-like lustrous materials do not overlap each other. This makes it easier for the scale-like lustrous materials to be arranged parallel to the lustrous coating film. Furthermore, even when the occupancy rate of the lustrous material is low, the impression of the coating film being dense is strengthened, and the metallic texture is enhanced. "The scale-like lustrous materials do not overlap each other" means that, in the cross section of the multilayer coating film, some or all of the scale-like lustrous materials do not overlap with other scale-like lustrous materials in the thickness direction. It is not necessary for the scale-like lustrous materials to be in contact with each other. For example, when the multilayer coating film is viewed from the normal direction, if some or all of the scale-like lustrous materials appear to overlap each other, the scale-like lustrous materials overlap each other in the thickness direction.

[0034] In particular, it is preferable that 80% or more of the scale-like luminous materials contained in the lustrous coating film do not overlap with other scale-like luminous materials. The overlapping ratio of scale-like luminous materials is determined as follows: First, a cross-section of the multilayer coating film is imaged using an electron microscope. In the obtained cross-section, one or more scale-like luminous materials that are closest to the clear coating film of the lustrous coating film are designated as reference luminous materials. Mark the scale-like luminous materials that overlap the reference luminous materials in the thickness direction. Furthermore, mark the scale-like luminous materials that overlap the marked luminous materials in the thickness direction. All marked luminous materials that can be seen in their entirety in the observation field (hereinafter sometimes referred to as overlapping luminous materials) are counted. At this time, one overlapping luminous material is not counted multiple times. The proportion of overlapping lustrous materials is determined by dividing the number of overlapping lustrous materials by the number of scaly lustrous materials that can be seen in their entirety in the observation field (i.e., the total of the reference lustrous materials and overlapping lustrous materials).

[0035] [Object to be coated] The material of the substrate is not particularly limited as long as it is suitable for an automobile body. Examples of the substrate include metal materials containing iron, copper, aluminum, tin, zinc, or alloys thereof. The shape of the substrate is also not particularly limited. The substrate may be in the form of a plate or may have a three-dimensional shape. The substrate constitutes at least a part of the body of, for example, a passenger car, truck, bus, or the like.

[0036] The substrate may be degreased and / or surface-treated. Examples of surface treatments include phosphate treatment, chromate treatment, zirconium conversion treatment, and composite oxide treatment. After surface treatment, the metal material is preferably primed with an electrodeposition paint. The electrodeposition paint may be either cationic or anionic.

[0037] [Multi-layer coating] The multi-layer coating film comprises a color coating film, a glitter coating film, and a clear coating film in this order.

[0038] The specular gloss of the multilayer coating film is not particularly limited. The 60-degree specular gloss of the multilayer coating film may be 100% or more and 180% or less. The 60-degree specular gloss is measured in accordance with JIS Z 8741, Specular Gloss - Measurement Method. Specifically, light is irradiated at an incident angle of 60 degrees with respect to the normal of the multilayer coating film, and the luminous flux φ of the reflected light at a reflection angle of 60 degrees is S Under the same conditions, light is irradiated onto a flat surface of glass with a refractive index of 1.567, and the luminous flux φ0 of the reflected light is measured. S The 60-degree specular gloss is calculated by dividing this by the luminous flux φ0 and multiplying the result by 100. The 60-degree specular gloss is the average value of the 60-degree specular gloss of five different samples.

[0039] <Colored coating> The pigmented coating conceals the texture and color of the substrate and imparts a white hue to the automobile body.

[0040] The thickness of the colored coating film is not particularly limited. From the viewpoint of hiding power, the thickness of the colored coating film may be 15 μm or more and 50 μm or less, 18 μm or more and 45 μm or less, or 20 μm or more and 40 μm or less. When the thickness of the colored coating film is within this range, the texture and color of the coated object are easily concealed without showing through the colored coating film. The thickness of the colored coating film is measured, for example, using an electromagnetic film thickness meter. The thickness of the colored coating film is the average thickness of the colored coating film for five different samples. The thickness of other layers can be measured and calculated in a similar manner.

[0041] The black-and-white hiding film thickness of the colored coating film is preferably 80 μm or less, more preferably 10 μm to 70 μm, and particularly preferably 15 μm to 60 μm. The black-and-white hiding film thickness is measured using a black-and-white checkerboard pattern hiding test paper as specified in JIS K5600-4-1, 4.1.2. Specifically, the hiding test paper is attached to a steel plate, and the paint is applied at an angle so that the film thickness changes continuously. After the paint has dried or cured, the painted surface is visually observed under diffused daylight. The minimum film thickness at which the black-and-white border of the checkerboard pattern on the hiding test paper becomes invisible is the black-and-white hiding film thickness. This film thickness can also be measured using an electromagnetic film thickness meter.

[0042] Optical IC illuminated at a 45-degree angle onto the surface of a colored coating 45 The brightness CL based on the spectral reflectance of light received at a 45-degree angle to the specular reflected light * 45 is preferably 70 or more and 95 or less. Since the colored coating film has high brightness in the shade and the occupancy rate of the luster material is small, the multi-layer coating film appears whiter in the region on the shade side than the super highlight.

[0043] (white pigment) The colored coating film contains a white pigment. There are no particular limitations on the white pigment. Examples of white pigments include titanium dioxide, zinc oxide, and silica. These may be used alone or in combination of two or more. Titanium dioxide is preferred because of its high refractive index. Titanium dioxide may be of the rutile type or the anatase type. Of these, rutile type titanium dioxide is preferred from the viewpoint of weather resistance. The surface of titanium dioxide may be treated with an inorganic compound such as silica, zirconium, or aluminum.

[0044] The primary particle diameter of the white pigment is not particularly limited. From the viewpoint of hiding power, the primary particle diameter of the white pigment is preferably 100 nm or more and 500 nm or less, more preferably 200 nm or more and 400 nm or less. The primary particle diameter can be measured from an electron microscope image of the cross section of the multilayer coating film using image processing software.

[0045] The amount of the white pigment is not particularly limited. * 45 is added so that the lightness CL of the colored coating film is 70 or more and 90 or less. * 45 is added so that the white pigment content is 70 to 95. Specifically, the amount of the white pigment is preferably 5 to 40% by mass of the colored coating film, more preferably 10 to 30% by mass, and even more preferably 15 to 25% by mass. The amount of the white pigment is preferably 50 to 200 parts by mass, and more preferably 80 to 150 parts by mass, per 100 parts by mass of the first resin described below.

[0046] (First resin) The colored coating film contains, in addition to the white pigment, a vehicle such as a first resin, in which the white pigment is dispersed.

[0047] The first resin is not particularly limited. The first resin preferably includes a cured product of a first thermosetting resin. The first resin is obtained, for example, by curing a first thermosetting resin formed from a crosslinkable functional group and a base resin. A first curing agent may be used for curing.

[0048] Examples of the crosslinkable functional group include a carboxy group, a hydroxyl group, an epoxy group, a silanol group, and a (meth)acryloyl group.

[0049] Examples of base resins include acrylic resins, polyester resins, alkyd resins, polyurethane resins, epoxy resins, and fluororesins. The epoxy resin may be a urethane-modified epoxy resin. The polyester resin may be a urethane-modified polyester resin. The acrylic resin may be a urethane-modified acrylic resin. Each urethane-modified resin has a urethane bond in the resin skeleton. These may be used alone or in combination of two or more. Among these, acrylic resins and urethane-modified polyesters are preferred in terms of improved chipping resistance.

[0050] The acrylic resin can be obtained, for example, by copolymerizing an α,β-ethylenically unsaturated carboxylic acid, a (meth)acrylic acid ester having a functional group such as a hydroxyl group, an amide group, or a methylol group, another (meth)acrylic acid ester, and styrene.

[0051] Urethane-modified polyesters are obtained by reacting hydroxyl-containing polyesters with aliphatic diisocyanate compounds. Hydroxyl-containing polyesters are prepared by polycondensation of polycarboxylic acids and / or acid anhydrides with polyhydric alcohols. Examples of aliphatic diisocyanate compounds include hexamethylene diisocyanate, trimethylhexamethylene diisocyanate, cyclohexane-1,4-diisocyanate, dicyclohexylmethane-4,4-diisocyanate, and methylcyclohexane diisocyanate.

[0052] The amount of the first resin is not particularly limited. In order to easily form a uniform coating film, the amount of the first resin is preferably from 60 to 95% by mass of the colored coating film, more preferably from 70 to 90% by mass, and even more preferably from 75 to 85% by mass.

[0053] The glass transition temperature (Tg) of the first resin is not particularly limited. From the viewpoint of coating hardness and smoothness, the Tg of the first resin is preferably −40° C. or higher and 20° C. or lower, and more preferably −30° C. or higher and 10° C. or lower. Tg is measured by a differential scanning calorimeter (DSC) in accordance with JIS K 7121.

[0054] (others) The colored coating film may further contain other pigments depending on the hiding power, etc. Examples of other pigments include metallic pigments, anti-rust pigments, color pigments other than white pigments, and extender pigments. Examples of extender pigments include calcium carbonate, barium sulfate, clay, and talc.

[0055] The colored coating film may also contain various additives as needed, such as ultraviolet absorbers, antioxidants, antifoaming agents, surface conditioners, dispersants, and pinhole prevention agents.

[0056] <Glitter coating> The glossy coating film gives the automobile body a metallic texture.

[0057] The thickness of the glittering coating film is not particularly limited. The thickness of the glittering coating film is preferably 0.05 μm or more and 1.0 μm or less, since this makes it easier for the glittering material to be aligned parallel to the coating film. The thickness of the glittering coating film may be 0.1 μm or more, or 0.3 μm or more. The thickness of the glittering coating film may be 0.8 μm or less, or 0.7 μm or less.

[0058] (shining material) The lustrous coating film contains a lustrous material. The lustrous material is not particularly limited as long as it reflects light. Among these, a scaly lustrous material is preferred because it allows the lustrous coating film to be made thinner and the metallic texture is easily improved. The aspect ratio of the scaly lustrous material is, for example, 2 or more. The aspect ratio is the ratio of the major axis of one main surface of the scaly lustrous material to the distance (thickness) between the two main surfaces of the scaly lustrous material: major axis / thickness. The aspect ratio of the scaly lustrous material may be 10 or more and 1000 or less.

[0059] The lustrous coating film may contain, together with the scaly lustrous material, other lustrous materials (lustrous materials with an aspect ratio of less than 2). However, the content of the other lustrous materials is preferably 10% by mass or less, and more preferably 5% by mass or less, of the total lustrous materials. This makes it easier for the scaly lustrous material to be aligned parallel to the coating film.

[0060] The major axis of the luminous material is not particularly limited. From the viewpoint of ease of adjusting the occupancy rate, the major axis of the luminous material is preferably 1 μm or more and 80 μm or less, and more preferably 3 μm or more and 50 μm or less. The major axis is calculated by observing the multilayer coating film from its normal direction using an electron microscope. In the observation field, the area corresponding to the luminous material and the other areas are binarized using image processing software. Next, 20 luminous materials are randomly selected, and the longest diameter of each is measured. The average of these measurements is the major axis of the luminous material.

[0061] The thickness of the luster material, particularly the scaly luster material, is preferably 0.05 μm or more and 0.3 μm or less. This allows the luster coating film to be thin. The thickness of the luster material is preferably 0.25 μm or less, more preferably 0.2 μm or less. The thickness may be calculated by observing the cross section of the multilayer coating film with an electron microscope. In the observation field, the area corresponding to the luster material and the other areas are binarized using image processing software. Next, 20 luster materials are randomly selected, and the length of their thickest part is measured. The average of these measurements is the thickness of the luster material.

[0062] The average particle size of the luster material is not particularly limited. In terms of facilitating improved luster, the average particle size of the luster material is preferably 2 μm or more and 50 μm or less, and more preferably 5 μm or more and 35 μm or less. The average particle size refers to the volume average particle size D50. The volume average particle size D50 can be measured using a laser Doppler particle size analyzer (for example, "Microtrac UPA150" manufactured by Nikkiso Co., Ltd.).

[0063] The glittering material is not particularly limited. * 5 / L * 15 tends to become large, so luminous materials that do not use multiple reflection interference as a coloring function are preferred. Examples of such luminous materials include metal particles. Specific examples include particles of aluminum, copper, zinc, iron, nickel, tin, aluminum oxide, and alloys containing these. The luminous materials may be colored. These may be used alone or in combination of two or more. Mica is a typical luminous material that uses multiple reflection interference as a coloring function. Even when metal particles with high reflectivity are used, high brightness L can be achieved by keeping their occupancy low. * 45 can be achieved.

[0064] Among these, flaky metal particles are more preferred, and flaky aluminum particles are more preferred in that a high level of brilliance can be obtained with a small amount.

[0065] The total amount of the luster material is preferably 3% to 30% by mass of the luster coating film, and more preferably 5% to 25% by mass, which makes it easier for the luster material to have an occupancy rate of 10% to 30%.

[0066] (Viscosity adjuster) The glittering coating film may contain a viscosity modifier. The viscosity modifier adjusts the viscosity of the glittering pigment dispersion (Y), which is a material for the glittering coating film. In the glittering pigment dispersion (Y) immediately after application, the glittering material is aligned parallel to the coating film. However, when the liquid components contained in the glittering pigment dispersion (Y) flow, the glittering material also flows, disrupting its alignment. By appropriately adjusting the viscosity of the glittering pigment dispersion (Y), the flow of the liquid components is suppressed in the glittering coating film after application and before curing, and disruption of the alignment of the glittering material is also suppressed. Therefore, the glittering material is more likely to be maintained in an aligned state parallel to the coating film.

[0067] The viscosity modifier is not particularly limited. Examples of viscosity modifiers include silica-based fine powders, mineral-based viscosity modifiers, barium sulfate fine powder, polyamide-based viscosity modifiers, organic resin fine particle viscosity modifiers, diurea-based viscosity modifiers, urethane association-type viscosity modifiers, acrylic swelling-type polyacrylic acid-based viscosity modifiers, and cellulose-based viscosity modifiers. These may be used alone or in combination of two or more. Among these, cellulose-based viscosity modifiers are preferred because they allow the lustrous material to be easily dispersed and have excellent quick-drying properties.

[0068] Examples of mineral viscosity modifiers include swellable layered silicates having a 2:1 crystal structure. Specific examples include smectite clay minerals such as natural or synthetic montmorillonite, saponite, hectorite, stevensite, beidellite, nontronite, bentonite, and laponite; swellable mica clay minerals such as Na-type tetrasilicic fluorine mica, Li-type tetrasilicic fluorine mica, Na-salt-type fluorine taeniolite, and Li-type fluorine taeniolite; vermiculite; and substitution products and derivatives thereof.

[0069] Examples of polyacrylic acid viscosity modifiers include sodium polyacrylate and polyacrylic acid-(meth)acrylic acid ester copolymers. Commercially available polyacrylic acid viscosity modifiers include Primal ASE-60, Primal TT615, and Primal RM5 (all manufactured by The Dow Chemical Company), and SN Thickener 613, SN Thickener 618, SN Thickener 630, SN Thickener 634, and SN Thickener 636 (all manufactured by San Nopco). The acid value of the solid content of the polyacrylic acid viscosity modifier is not particularly limited. The acid value of the solid content may be 30 mgKOH / g or more and 300 mgKOH / g or less, or 80 mgKOH / g or more and 280 mgKOH / g or less.

[0070] Examples of cellulose-based viscosity modifiers include cellulose acetate butyrate (CAB), carboxymethyl cellulose, methyl cellulose, hydroxyethyl cellulose, hydroxyethyl methyl cellulose, hydroxypropyl methyl cellulose, methyl cellulose, and cellulose nanofiber gel. These may be used alone or in combination of two or more. Among these, CAB is preferred.

[0071] The amount of viscosity modifier is not particularly limited. For example, the amount of viscosity modifier may be 0.1 parts by mass or more and 10 parts by mass or less, 0.5 parts by mass or more and 5 parts by mass or less, or 1.0 parts by mass or more and 3.0 parts by mass or less, relative to 100 parts by mass of the luster pigment dispersion. This makes it easier to suppress disorder in the arrangement of the luster pigment.

[0072] (Second resin) The glittering coating film may contain a resin component (second resin). The second resin contains, for example, a cured product of a thermosetting resin similar to the first resin. However, it is desirable that the amount of the second resin is small. A small amount of the second resin makes it easier to make the glittering coating film thin. When the glittering coating film is thin, it is easier to suppress the disorder of the orientation of the glittering material, and the glittering material is more likely to be aligned parallel to the surface of the coating film.

[0073] The amount of the second resin is preferably 15% by mass or less, more preferably 10% by mass or less, and particularly preferably 5% by mass or less of the glittering pigment dispersion, in order to facilitate the formation of a thin glittering coating film.

[0074] (others) The glittering coating film may contain other pigments besides the luster material depending on the hiding power, etc. Examples of other pigments include anti-rust pigments, coloring pigments (including white pigments), and the above-mentioned extender pigments. In particular, the glittering coating film may contain a white pigment (particularly titanium dioxide). In order to facilitate the alignment of the scaly luster material parallel to the coating film, the content of the other pigment (particularly titanium dioxide) is preferably 10% by mass or less, and more preferably 2% by mass or less, of the glittering pigment dispersion. The content of the other pigment (particularly titanium dioxide) may be 0.01% by mass or more, or may be 0.1% by mass or more, of the glittering pigment dispersion.

[0075] The glitter coating film may contain various additives as needed, such as ultraviolet absorbers, antioxidants, antifoaming agents, anti-settling agents, dispersants, and surface conditioners.

[0076] <Clear coating> The clear coating film protects the color coating film and the luster coating film. There are no particular restrictions on the clear coating film, and it has the same structure as conventionally known clear coating films.

[0077] The thickness of the clear coating film is not particularly limited. From the viewpoint of scratch resistance, the thickness of the clear coating film is preferably 10 μm or more, more preferably 15 μm or more. In order to prevent the whiteness and metallic texture from being easily impaired, the thickness of the clear coating film may be 50 μm or less, or may be 40 μm or less.

[0078] (Third resin) The clear coating film contains, for example, a third resin. The third resin preferably contains a cured product of a third thermosetting resin. Specifically, the third resin is obtained by curing a third thermosetting resin formed from a crosslinkable functional group and a base resin. A second curing agent may be used for curing.

[0079] Examples of the third thermosetting resin include the same resins as those exemplified as the first thermosetting resin. The Tg of the third resin is not particularly limited. From the viewpoint of coating hardness and smoothness, the Tg of the third resin is preferably −40° C. or higher and 20° C. or lower, and more preferably −30° C. or higher and 10° C. or lower.

[0080] (others) The clear coating film may contain a pigment to the extent that transparency is not impaired. The pigment is not particularly limited, and one or a combination of two or more conventionally known pigments may be used. The amount of pigment added is not particularly limited. For example, the amount of pigment added may be 30 parts by mass or less, and may be 0.01 to 10 parts by mass, per 100 parts by mass of the solid content of the third resin.

[0081] The clear coating film may contain various additives as needed, such as ultraviolet absorbers, antioxidants, antifoaming agents, surface conditioners, and pinhole inhibitors.

[0082] 2 is a cross-sectional view showing a schematic view of a portion of an automobile body according to this embodiment. The automobile body 100 comprises an object 10 to be coated and a multilayer coating film 20. The multilayer coating film 20 comprises, in this order, a colored coating film 21, a glitter coating film 22, and a clear coating film 23. The glitter coating film 22 contains a glittering material 221.

[0083] 3 is a cross-sectional view showing a schematic view of a portion of the glittering coating film according to this embodiment. In the illustrated example, the acute angle formed by an approximate straight line L0 of the surface of the glittering coating film 22 and an approximate straight line L1 of the surface of the glittering material 221 is approximately 0 degrees. In other words, the glittering material 221 is parallel to the surface of the glittering coating film 22.

[0084] B. Automobile body manufacturing method Automobile bodies are manufactured by forming a colored coating film, a glitter coating film, and a clear coating film in this order on a substrate. When the glitter coating film is formed, the colored coating film may be cured or uncured. When the clear coating film is formed, the glitter coating film may be cured or uncured. From the viewpoints of productivity, adhesion, and water resistance, it is preferable to laminate each coating film without curing it, and then heat the laminate to simultaneously cure these three uncured coating films.

[0085] As used herein, curing is a concept that includes solidification. That is, curing in this specification means that the coating film loses its fluidity, regardless of whether a chemical reaction is involved. Specifically, curing in this specification is synonymous with "cured and dried" as defined in JIS K 5500 (paint terminology). That is, curing refers to a state (dry and hard) in which a test piece is pinched firmly between the thumb and index finger at the center, no fingerprint indentation is left on the coating surface, no movement of the coating film is felt, and no scratch marks are left when the coating surface is rubbed rapidly and repeatedly with a fingertip. As used herein, "uncured" refers to a state other than the above-mentioned cured state, including a semi-cured state.

[0086] The automobile body is preferably manufactured by the following method: That is, the method for manufacturing an automobile body comprises the steps of applying a colored paint onto an object to be coated to form an uncured colored paint film, applying a glitter pigment dispersion onto the uncured colored paint film to form an uncured glitter paint film, applying a clear paint onto the uncured glitter paint film to form an uncured clear paint film, and curing the uncured colored paint film, the uncured glitter paint film, and the uncured clear paint film to obtain a multilayer paint film. FIG. 4 is a flowchart showing a method for manufacturing an automobile body according to this embodiment.

[0087] Light irradiated from a 45-degree angle onto the surface of the multi-layer coating I 45 The brightness L based on the spectral reflectance of light received at a 45-degree angle to the specular reflected light * 45 is between 70 and 80. 45The brightness L based on the spectral reflectance of light received at an angle of 15 degrees relative to the specular reflection light * 5 and the above light I 45 The brightness L based on the spectral reflectance of light received at an angle of 15 degrees relative to the specular reflection light * Ratio to 15:L * 5 / L * 15 is 1.2 or more and 2.5 or less. The occupancy rate of the lustrous material as viewed from the surface of the multi-layer coating film is 10% or more and 30% or less. The graininess G on the surface of the multi-layer coating film is 1.0 or more and 3.0 or less.

[0088] (1) Step of forming an uncured colored coating film (S11) A colored coating (X) is applied to the substrate to form an uncured colored coating film.

[0089] The coating method is not particularly limited. Examples of coating methods include air spray coating, airless spray coating, rotary atomization coating, and curtain coat coating. These methods may be combined with electrostatic coating. Among them, rotary atomization electrostatic coating is preferred from the viewpoint of coating efficiency. For rotary atomization electrostatic coating, a rotary atomization electrostatic coater, commonly known as a "micro-microbell (μμbell)," a "microbell (μbell)," or a "metallicbell (metabell)," is used.

[0090] There are no particular limitations on the amount of colored coating material (X) applied. For example, the colored coating material (X) is applied so that the thickness of the colored coating film after curing is 15 μm or more and 50 μm or less.

[0091] After applying the colored coating (X), pre-drying (also called preheating) may be performed. This suppresses bumping of the solvent contained in the colored coating film during the curing process, making it easier to prevent popping. Furthermore, pre-drying suppresses mixing of the uncured colored coating film and the luster coating, making it harder for a mixed layer to form. This makes it easier to improve the appearance of the resulting multi-layer coating film.

[0092] The conditions for pre-drying are not particularly limited. Examples of pre-drying include leaving the film at a temperature of 20°C to 25°C for 15 to 30 minutes, or heating the film at a temperature of 50°C to 100°C for 30 seconds to 10 minutes.

[0093] <Colored paint (X)> The colored paint (X) contains the above-mentioned white pigment and first thermosetting resin. The colored paint (X) also contains a first curing agent, a first solvent, various additives, etc. as necessary. The colored paint (X) is prepared by diluting a mixture of the white pigment, the first thermosetting resin, the first curing agent, various additives, etc. with the first solvent. The colored paint (X) may be a one-component paint or a multi-component paint such as a two-component paint.

[0094] The viscosity of the colored coating material (X) is not particularly limited. The viscosity of the colored coating material (X) measured at 20° C. with a Brookfield viscometer is, for example, 500 cps / 6 rpm or more and 6000 cps / 6 rpm or less.

[0095] The solid content of the colored coating material (X) is not particularly limited. The solid content of the colored coating material (X) is preferably 30% by mass or more and 70% by mass or less. The solid content of the colored coating material (X) is all components of the colored coating material (X) excluding the first solvent.

[0096] (1st thermosetting resin) The first thermosetting resin is formed from a crosslinkable functional group and a base resin, the details of which are as described above.

[0097] The amount of the first thermosetting resin is not particularly limited. When the first curing agent is contained, the solid content mass of the first thermosetting resin is preferably 60% by mass or more and 90% by mass or less, and more preferably 70% by mass or more and 85% by mass or less, of the total solid content mass of the first thermosetting resin and the first curing agent.

[0098] (First hardener) The first curing agent is not particularly limited and may be appropriately selected depending on the first thermosetting resin. Examples of first curing agents include amino resins, urea resins, polyisocyanate compounds, epoxy group-containing compounds, carboxy group-containing compounds, carbodiimide group-containing compounds, hydrazide group-containing compounds, and semicarbazide group-containing compounds. Polyisocyanate compounds include blocked polyisocyanate compounds in which the isocyanate group is blocked with a blocking agent. These compounds may be used alone or in combination of two or more. Among these, amino resins and polyisocyanate compounds are preferred in terms of the performance and cost of the resulting coating film. Amino resins can be obtained, for example, by condensing an amino compound such as melamine, benzoguanamine, or urea with formaldehyde, followed by etherification with a lower monohydric alcohol. Details of polyisocyanate compounds will be described later.

[0099] The amount of the first curing agent is not particularly limited. From the viewpoint of curability, the solid content mass of the first curing agent is preferably 10% by mass or more and 40% by mass or less of the total solid content mass of the first thermosetting resin and the first curing agent, more preferably 15% by mass or more and 30% by mass or less, and particularly preferably 15% by mass or more and 25% by mass or less.

[0100] (First solvent) The first solvent is not particularly limited. The first solvent may be water (deionized water), an organic solvent, or a combination thereof. Among them, water is preferred from the viewpoint of low VOC (Volatile Organic Compounds). The proportion of water in the first solvent is preferably 50% by mass or more, and more preferably 80% by mass or more.

[0101] Examples of organic solvents include ester solvents such as ethyl acetate, butyl acetate, isopropyl acetate, ethylene glycol monoethyl ether acetate, propylene glycol monomethyl ether acetate, and propylene glycol monoethyl ether acetate; Examples of suitable solvents include ether solvents such as propylene glycol monomethyl ether, ethylene glycol monomethyl ether, methyl methoxybutanol, ethoxypropanol, ethylene glycol isopropyl ether, ethylene glycol t-butyl ether, ethylene glycol monoethyl ether, ethylene glycol monobutyl ether, methoxybutanol, and propylene glycol monobutyl ether; alcohol solvents such as methanol, ethanol, butanol, and propyl alcohol; ketone solvents such as acetone, methyl ethyl ketone, and methyl isobutyl ketone; aliphatic hydrocarbon solvents such as Swazol, Shellsol, and mineral spirits; and aromatic solvents such as xylene, toluene, Solvesso-100 (S-100), and Solvesso-150 (S-150). These may be used alone or in combination of two or more.

[0102] The amount of the first solvent is not particularly limited and is set appropriately depending on the solid content and viscosity of the colored coating material (X). For example, the first solvent is added so that the solid content of the colored coating material (X) is 30% by mass or more and 70% by mass or less, and the viscosity of the colored coating material (X) measured with a Brookfield viscometer at 20°C is 500 cps / 6 rpm or more and 6000 cps / 6 rpm or less.

[0103] When water is used as the first solvent, a first thermosetting resin having a hydrophilic group may be used. Neutralizing the hydrophilic group of the first thermosetting resin to form an alkali salt makes the first thermosetting resin water-soluble or water-dispersible. Examples of hydrophilic groups include carboxyl groups, hydroxyl groups, methylol groups, amino groups, sulfonic acid groups, and polyoxyethylene bonds. Examples of neutralizing agents include alkaline substances such as sodium hydroxide and amine compounds.

[0104] The first thermosetting resin can be prepared in an aqueous dispersion state by emulsion polymerization of the raw material monomers of the first thermosetting resin in the presence of a surfactant or a water-soluble resin. Alternatively, the first thermosetting resin can be dispersed in water using an emulsifier. In these cases, the first thermosetting resin may not contain hydrophilic groups, or may contain only a small amount of hydrophilic groups.

[0105] (others) The colored coating (X) also contains the pigments and various additives exemplified as those contained in the colored coating film.

[0106] (2) Step of forming an uncured glossy coating film (S12) The glitter pigment dispersion (Y) is applied onto the uncured colored coating film to form an uncured glitter coating film.

[0107] The coating method is not particularly limited. Examples of the coating method include the same methods as those used for coating colored paints. Among these, rotary atomization electrostatic coating is preferred from the viewpoint of coating efficiency.

[0108] The amount of the glittering pigment dispersion (Y) to be applied is not particularly limited. For example, the glittering pigment dispersion (Y) is applied so that the thickness of the glittering coating film in the resulting multilayer coating film is 0.05 μm or more and 1.0 μm or less.

[0109] After the application of the glitter pigment dispersion (Y), pre-drying may be carried out. This quickly reduces the fluidity of the glitter coating film, making it easier to suppress the flow of the glitter material. The conditions for pre-drying are not particularly limited and may be the same as those for pre-drying a colored coating film.

[0110] <Glitter pigment dispersion (Y)> The brilliant pigment dispersion (Y) contains a brilliant pigment. The brilliant pigment dispersion (Y) optionally contains a viscosity modifier, a second solvent, and the like. The brilliant pigment dispersion (Y) is prepared by diluting a mixture of the brilliant pigment, the viscosity modifier, various additives, and the like with the second solvent.

[0111] The viscosity of the luster pigment dispersion (Y) is not particularly limited. The viscosity of the luster pigment dispersion (Y) measured with a Brookfield viscometer at 20°C is preferably 20 cps / 6 rpm or more and 3000 cps / 6 rpm or less, since this makes it easier to suppress disorder in the arrangement of the luster pigment.

[0112] The solid content of the glittering pigment dispersion (Y) is preferably 0.1% by mass or more and 10.0% by mass or less. This makes it easy to form a thin glittering coating film. The solid content of the glittering pigment dispersion (Y) is preferably 9.0% by mass or less, more preferably 8.0% by mass or less, and particularly preferably 7.5% by mass or less. The solid content of the glittering pigment dispersion (Y) is all components of the glittering pigment dispersion (Y) excluding the second solvent.

[0113] In particular, when the brilliant pigment dispersion (Y) is aqueous, i.e., when the second solvent contains 50% by mass or more of water, the solid content of the brilliant pigment dispersion (Y) is preferably 3.5% by mass or more, more preferably 4.0% by mass or more, and particularly preferably 4.5% by mass or more. When the second solvent contains 50% by mass or more of water, the solid content of the brilliant pigment dispersion (Y) is preferably 8.5% by mass or less, more preferably 8.0% by mass or less, and particularly preferably 7.5% by mass or less.

[0114] When the bright pigment dispersion (Y) is solvent-based, i.e., when the second solvent contains 50% by mass or more of an organic solvent, the solid content of the bright pigment dispersion (Y) is preferably 1.0% by mass or more, more preferably 2.0% by mass or more. When the second solvent contains 50% by mass or more of an organic solvent, the solid content of the bright pigment dispersion (Y) is preferably 5.0% by mass or less, more preferably 3.5% by mass or less.

[0115] (shining material) Details of the glittering material are as described above.

[0116] The amount of the luster pigment is not particularly limited. The amount of the luster pigment may be, for example, 0.05% by mass or more and 3.0% by mass or less, 0.2% by mass or more and 1.5% by mass or less, or 0.3% by mass or more and 0.8% by mass or less of the luster pigment dispersion (Y). This makes it easy for the occupancy rate of the luster pigment to be 10% or more and 30% or less.

[0117] (Viscosity adjuster) Details of the viscosity modifier are as described above.

[0118] The amount of the viscosity adjuster is determined by the amount of the bright pigment dispersion (Y). 1 The content is preferably from 10% by mass to 30% by mass, and more preferably from 10% by mass to 30% by mass, which makes it easier to prevent the arrangement of the metallic pigment from becoming disordered.

[0119] (Second solvent) The second solvent is not particularly limited. The second solvent may be water, an organic solvent, or a combination thereof. Among them, water is preferred from the viewpoint of low VOC. The proportion of water in the second solvent is preferably 50% by mass or more, and more preferably 80% by mass or more. Examples of organic solvents used in the second solvent include the same organic solvents as those exemplified as the first solvent.

[0120] The amount of the second solvent is not particularly limited and is set appropriately depending on the solid content and viscosity of the glittering pigment dispersion (Y). For example, the second solvent is added so that the solid content of the glittering pigment dispersion (Y) is 0.1% by mass or more and 10.0% by mass or less, and the viscosity of the glittering pigment dispersion (Y) measured at 20°C with a B-type viscometer is 20 cps / 6 rpm or more and 3000 cps / 6 rpm or less.

[0121] (others) The glitter pigment dispersion (Y) also contains various additives exemplified as those contained in the glitter coating film.

[0122] For example, a dispersant is added to enhance the dispersibility of the luster pigment. The dispersant is not particularly limited and is appropriately selected depending on the second solvent, luster pigment, etc.

[0123] When the bright pigment dispersion (Y) is aqueous, examples of dispersants that can be used include inorganic dispersants such as phosphates and polyphosphates; polymeric dispersants such as polycarboxylic acid polyethylene glycols and naphthalene sulfonate-formalin condensation dispersants; and low molecular weight dispersants such as alkyl sulfonic acids, quaternary ammonium salts, and higher alcohol alkylene oxides. Examples of phosphates include sodium hexametaphosphate, sodium pyrophosphate, and sodium phosphate.

[0124] When the bright pigment dispersion (Y) is a solvent-based dispersion, the dispersant used may be, for example, a polymeric dispersant such as a polycarboxylic acid partial alkyl ester-based, polyether-based, or polyalkylene polyamine-based dispersant.

[0125] The amount of the dispersant is not particularly limited and may be, for example, from 0.01% to 3% by mass, or from 0.1% to 1.0% by mass, of the effective pigment dispersion (Y).

[0126] The surface conditioner is added to control the surface tension of the glittering coating film, which makes it easier for the glittering material to align parallel to the coating film, and also improves the adhesion between layers.

[0127] The surface conditioner is not particularly limited. Examples of the surface conditioner include silicone-based, acrylic-based, vinyl-based, and fluorine-based surface conditioners. These may be used alone or in combination of two or more. Among them, silicone-based surface conditioners are preferred from the viewpoint of the brightness and water resistance of the glossy coating film. Examples of silicone-based surface conditioners include polydimethylsiloxane and modified silicones obtained by modifying the same. Examples of modified silicones include polyether-modified products, acrylic-modified products, and polyester-modified products.

[0128] Commercially available surface conditioners include, for example, the BYK series (manufactured by BYK-Chemie), the Tego series (manufactured by Evonik), the Granol series, the Polyflow series (all manufactured by Kyoeisha Chemical Co., Ltd.), and the Disparlon series (manufactured by Kusumoto Chemicals Co., Ltd.).

[0129] The amount of the surface conditioner is not particularly limited. The amount of the surface conditioner is preferably 0.1% by mass or more and 10% by mass or less, more preferably 0.2% by mass or more and 8% by mass or less, and particularly preferably 0.4% by mass or more and 6% by mass or less, of the glittering pigment dispersion (Y). When the surface conditioner is used in this range, the surface tension of the glittering coating film is reduced, and the wettability of the glittering pigment dispersion (Y) to the uncured colored coating film is easily improved.

[0130] (3) Step of forming an uncured clear coating film (S13) A clear coating (Z) is applied on the glossy coating to form an uncured clear coating.

[0131] The coating method is not particularly limited. Examples of the coating method include the same methods as those used for coating colored paints. Among these, rotary atomization electrostatic coating is preferred from the viewpoint of coating efficiency.

[0132] There are no particular limitations on the amount of clear coating material (Z) applied. The clear coating material (Z) is applied, for example, so that the thickness of the clear coating film after curing is 25 μm or more and 45 μm or less.

[0133] <Clear paint (Z)> The clear coating material (Z) is not particularly limited, and conventionally known clear coating materials can be used. The form of the clear coating material (Z) is also not particularly limited. The clear coating material (Z) may be a powder, water-based, or solvent-based.

[0134] The clear coating material (Z) contains the third thermosetting resin. The clear coating material (Z) contains a second curing agent, a third solvent, various additives, etc. as needed. The clear coating material (Z) is prepared by diluting a mixture of the third thermosetting resin, the second curing agent, various additives, etc. with the third solvent. The clear coating material (Z) may be a one-component coating material, or may be a multi-component coating material such as a two-component coating material.

[0135] The viscosity of the clear coating material (Z) is not particularly limited. The viscosity of the clear coating material (Z) measured at 20° C. with a B-type viscometer is, for example, 500 cps / 6 rpm or more and 6000 cps / 6 rpm or less.

[0136] The solid content of the clear coating material (Z) is not particularly limited and is, for example, 40% by mass or more and 60% by mass or less.

[0137] (Third thermosetting resin) The third thermosetting resin is formed from a crosslinkable functional group and a base resin, the details of which are as described above.

[0138] The one-component clear coating (Z) contains, for example, a polyepoxide and a polyacid as the third thermosetting resin. Specifically, the one-component clear coating (Z) contains, as the third thermosetting resin, an acrylic resin (1) containing an acid anhydride group, a polyester resin (2) containing a carboxyl group, and an acrylic resin (3) containing a hydroxyl group and an epoxy group. From the viewpoint of storage stability, the acid anhydride group of the acrylic resin (1) may be half-esterified with a low-molecular-weight alcohol or the like. Hereinafter, such a third thermosetting resin is referred to as an acid-epoxy curing resin composition. The acid-epoxy curing resin composition easily increases the solids content of the clear coating (Z). Furthermore, the acid-epoxy curing resin composition easily produces a clear coating film with excellent acid resistance.

[0139] In the acid-epoxy curing resin composition, curing proceeds through the mutual reaction of the above three types of polymers. The curing mechanism of the acid-epoxy curing resin composition is as follows. First, by heating, the acid anhydride group in the acrylic resin (1) reacts with the hydroxyl groups in the polyester resin (2) and the acrylic resin (3) to form a carboxyl group. This carboxyl group and the carboxyl group in the polyester resin (2) react with the epoxy group present in the acrylic resin (3) to form a crosslinking point. The crosslinking reaction begins at this crosslinking point.

[0140] The blending of the acrylic resin (1), the polyester resin (2), and the acrylic resin (3) is not particularly limited, and the blending of the acid-epoxy curing resin composition is carried out in amounts and by methods well known to those skilled in the art.

[0141] In particular, the molar ratio of the carboxyl groups of the acrylic resin (1) and the polyester resin (2) to the epoxy groups of the acrylic resin (3) is preferably 1 / 1.4 or more and 1 / 0.6 or less, more preferably 1 / 1.2 or more and 1 / 0.8 or less. This facilitates improving the curing properties of the clear coating material (Z). Furthermore, it facilitates obtaining a clear coating film that is resistant to yellowing.

[0142] The molar ratio of the carboxyl groups in the acrylic resin (1) to the hydroxyl groups in the polyester resin (2) and the acrylic resin (3) is preferably 1 / 2.0 or more and 1 / 0.5 or less, more preferably 1 / 1.5 or more and 1 / 0.7 or less. This facilitates the improvement of the curing properties of the clear coating material (Z). Furthermore, it facilitates the formation of a clear coating film with excellent water resistance.

[0143] The two-component clear coating (Z) is preferred because it is easy to improve the physical properties of the coating film. The two-component clear coating (Z) contains a separated third thermosetting resin and a second curing agent. The third thermosetting resin and the second curing agent are mixed immediately before use. Examples of combinations of the third thermosetting resin and the second curing agent include a carboxyl group-containing resin / epoxy group-containing resin, a hydroxyl group-containing resin / polyisocyanate compound, a hydroxyl group-containing resin / blocked isocyanate compound, and a hydroxyl group-containing resin / melamine resin. These are particularly suitable for forming a clear coating film.

[0144] Among these, it is preferable that the two-component clear coating (Z) contains a hydroxyl group-containing resin as the third thermosetting resin and a polyisocyanate compound as the second curing agent, in that the physical properties of the coating film are easily improved.

[0145] Specific examples of hydroxyl-containing resins include hydroxyl-containing acrylic resins, hydroxyl-containing polyester resins, hydroxyl-containing polyether resins, and hydroxyl-containing polyurethane resins. Among these, hydroxyl-containing acrylic resins and hydroxyl-containing polyester resins are preferred, and hydroxyl-containing acrylic resins are particularly preferred. These may be used alone or in combination of two or more.

[0146] The hydroxyl value of the hydroxyl-containing acrylic resin is not particularly limited. From the viewpoint of the scratch resistance and water resistance of the coating film, the hydroxyl value of the hydroxyl-containing acrylic resin is preferably from 80 mgKOH / g to 200 mgKOH / g, and more preferably from 100 mgKOH / g to 180 mgKOH / g.

[0147] The weight-average molecular weight of the hydroxyl-containing acrylic resin is not particularly limited. From the viewpoint of the acid resistance and smoothness of the coating film, the weight-average molecular weight of the hydroxyl-containing acrylic resin is preferably 2,500 to 40,000, more preferably 5,000 to 30,000. The weight-average molecular weight can be calculated from a chromatogram measured by gel permeation chromatography using the molecular weight of standard polystyrene as a reference. For example, an HLC8120GPC (manufactured by Tosoh Corporation) is used as the gel permeation chromatograph. For example, TSKgel G-4000HXL, TSKgel G-3000HXL, TSKgel G-2500HXL, or TSKgel G-2000HXL (all manufactured by Tosoh Corporation) is used as the column. The chromatography is performed, for example, using tetrahydrofuran as the mobile phase and a refractive index detector (RI) as the detector, at a measurement temperature of 40°C and a flow rate of 1 cc / min.

[0148] (Second curing agent) The second curing agent is not particularly limited and may be appropriately selected depending on the third thermosetting resin. Examples of the second curing agent include the same curing agents as those exemplified as the first curing agent.

[0149] For example, a polyisocyanate compound has at least two isocyanate groups in one molecule. Examples of the polyisocyanate compound include aliphatic polyisocyanates, alicyclic polyisocyanates, aliphatic polyisocyanates having aromatic rings in the molecule that are not bonded to isocyanate groups (araliphatic polyisocyanates), aromatic polyisocyanates, and derivatives of these polyisocyanates.

[0150] Examples of aliphatic polyisocyanates include trimethylene diisocyanate, tetramethylene diisocyanate, hexamethylene diisocyanate, pentamethylene diisocyanate, 1,2-propylene diisocyanate, 1,2-butylene diisocyanate, 2,3-butylene diisocyanate, 1,3-butylene diisocyanate, 2,4,4- or 2,2,4-trimethylhexamethylene diisocyanate, dimer acid diisocyanate, methyl 2,6-diisocyanatohexanoate (common name: lysine diisocyanate), aliphatic diisocyanates such as 2-isocyanatoethyl 2,6-diisocyanatohexanoate, 1,6-diisocyanato-3-isocyanatomethylhexane, 1,4,8-triisocyanatooctane, 1,6,11-triisocyanatoundecane, 1,8-diisocyanato-4-isocyanatomethyloctane, 1,3,6-triisocyanatohexane, and 2,5,7-trimethyl-1,8-diisocyanato-5-isocyanatomethyloctane.

[0151] Examples of alicyclic polyisocyanates include 1,3-cyclopentene diisocyanate, 1,4-cyclohexane diisocyanate, 1,3-cyclohexane diisocyanate, 3-isocyanatomethyl-3,5,5-trimethylcyclohexyl isocyanate (common name: isophorone diisocyanate), 4-methyl-1,3-cyclohexylene diisocyanate (common name: hydrogenated TDI), 2-methyl-1,3-cyclohexylene diisocyanate, 1,3- or alicyclic diisocyanates such as 1,4-bis(isocyanatomethyl)cyclohexane (common name: hydrogenated xylylene diisocyanate) or its mixture, methylenebis(4,1-cyclohexanediyl)diisocyanate (common name: hydrogenated MDI), norbornane diisocyanate, 4,4'-methylenebis(cyclohexyl isocyanate); 1,3,5-triisocyanatocyclohexane, 1,3,5-trimethylisocyanatocyclohexane, 2- (3-isocyanatopropyl)-2,5-di(isocyanatomethyl)-bicyclo(2.2.1)heptane, 2-(3-isocyanatopropyl)-2,6-di(isocyanatomethyl)-bicyclo(2.2.1)heptane, 3-(3-isocyanatopropyl)-2,5-di(isocyanatomethyl)-bicyclo(2.2.1)heptane, 5-(2-isocyanatoethyl)-2-isocyanatomethyl-3-(3-isocyanatopropyl)-bicyclo(2.2.1)heptane Alicyclic triisocyanates such as cyclohexane, 6-(2-isocyanatoethyl)-2-isocyanatomethyl-3-(3-isocyanatopropyl)-bicyclo(2.2.1)heptane, 5-(2-isocyanatoethyl)-2-isocyanatomethyl-2-(3-isocyanatopropyl)-bicyclo(2.2.1)heptane, and 6-(2-isocyanatoethyl)-2-isocyanatomethyl-2-(3-isocyanatopropyl)-bicyclo(2.2.1)heptane.

[0152] Examples of the araliphatic polyisocyanate include araliphatic diisocyanates such as methylenebis(4,1-phenylene)diisocyanate (common name: MDI), 1,3- or 1,4-xylylene diisocyanate or a mixture thereof, ω,ω'-diisocyanato-1,4-diethylbenzene, 1,3- or 1,4-bis(1-isocyanato-1-methylethyl)benzene (common name: tetramethylxylylene diisocyanate) or a mixture thereof; and araliphatic triisocyanates such as 1,3,5-triisocyanatomethylbenzene.

[0153] Examples of aromatic polyisocyanates include aromatic diisocyanates such as m-phenylene diisocyanate, p-phenylene diisocyanate, 4,4'-diphenyl diisocyanate, 1,5-naphthalene diisocyanate, 2,4-tolylene diisocyanate (common name: 2,4-TDI) or 2,6-tolylene diisocyanate (common name: 2,6-TDI) or mixtures thereof, 4,4'-toluidine diisocyanate, and 4,4'-diphenyl ether diisocyanate; aromatic triisocyanates such as triphenylmethane-4,4',4''-triisocyanate, 1,3,5-triisocyanatobenzene, and 2,4,6-triisocyanatotoluene; and aromatic tetraisocyanates such as 4,4'-diphenylmethane-2,2',5,5'-tetraisocyanate.

[0154] Examples of polyisocyanate derivatives include dimers, trimers, biurets, allophanates, uretdione, uretimine, isocyanurates, oxadiazinetrione, polymethylene polyphenyl polyisocyanate (crude MDI, polymeric MDI), and crude TDI of the above-mentioned polyisocyanates.

[0155] The polyisocyanate compounds may be used singly or in combination of two or more.

[0156] Among these, from the viewpoint of adhesion and compatibility, hexamethylene diisocyanate and 4,4'-methylenebis(cyclohexyl isocyanate) are preferred, and derivatives of hexamethylene diisocyanate are more preferred.

[0157] A prepolymer of the above polyisocyanate or its derivative may be used as the polyisocyanate compound. The prepolymer can be obtained by reacting a polyisocyanate or its derivative with a compound reactive therewith under conditions of excess isocyanate groups. The compound reactive with the polyisocyanate or its derivative is a compound having an active hydrogen group such as a hydroxyl group or an amino group. Examples of such compounds include polyhydric alcohols, low-molecular-weight polyester resins, amines, and water.

[0158] The polyisocyanate compound may be a blocked polyisocyanate compound, which can be obtained by blocking the isocyanate groups in the polyisocyanate or its derivatives with a blocking agent.

[0159] Examples of blocking agents include phenol compounds, lactam compounds, alcohols, ethers, oxime compounds, compounds having an active methylene group, mercaptan compounds, acid amide compounds, imide compounds, amine compounds, imidazole compounds, urea compounds, carbamic acid esters, imine compounds, sulfites, azole compounds, and ketone compounds.

[0160] Examples of phenolic compounds include phenol, cresol, xylenol, nitrophenol, ethylphenol, hydroxydiphenyl, butylphenol, isopropylphenol, nonylphenol, octylphenol, and methyl hydroxybenzoate.

[0161] Examples of lactam compounds include ε-caprolactam, δ-valerolactam, γ-butyrolactam and β-propiolactam.

[0162] Examples of alcohols include methanol, ethanol, propyl alcohol, butyl alcohol, amyl alcohol, lauryl alcohol, benzyl alcohol, glycolic acid, methyl glycolate, ethyl glycolate, butyl glycolate, lactic acid, methyl lactate, ethyl lactate, butyl lactate, methylol urea, methylol melamine, diacetone alcohol, 2-hydroxyethyl acrylate, and 2-hydroxyethyl methacrylate.

[0163] Examples of ethers include ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monobutyl ether, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, propylene glycol monomethyl ether, and methoxymethanol.

[0164] Examples of the oxime compounds include formamide oxime, acetamide oxime, acetoxime, methyl ethyl ketoxime, diacetyl monooxime, benzophenone oxime, and cyclohexane oxime.

[0165] Examples of compounds having an active methylene group include dimethyl malonate, diethyl malonate, ethyl acetoacetate, methyl acetoacetate, and acetylacetone.

[0166] Examples of mercaptan compounds include butyl mercaptan, t-butyl mercaptan, hexyl mercaptan, t-dodecyl mercaptan, 2-mercaptobenzothiazole, thiophenol, methylthiophenol, and ethylthiophenol.

[0167] Examples of the acid amide compounds include acetanilide, acetanisidide, acetotoluide, acrylamide, methacrylamide, acetic acid amide, stearic acid amide, and benzamide.

[0168] Examples of the imide compound include succinimide, phthalimide, and maleimide.

[0169] Examples of the amine compound include diphenylamine, phenylnaphthylamine, xylidine, N-phenylxylidine, carbazole, aniline, naphthylamine, butylamine, dibutylamine, and butylphenylamine.

[0170] Imidazole compounds include, for example, imidazole and 2-ethylimidazole.

[0171] Examples of urea compounds include urea, thiourea, ethyleneurea, ethylenethiourea, and diphenylurea.

[0172] An example of the carbamic acid ester is N-phenyl phenylcarbamate.

[0173] Imine compounds include, for example, ethyleneimine and propyleneimine.

[0174] Sulfites include, for example, sodium bisulfite and potassium bisulfite.

[0175] Examples of azole compounds include pyrazoles or pyrazole derivatives such as pyrazole, 3,5-dimethylpyrazole, 3-methylpyrazole, 4-benzyl-3,5-dimethylpyrazole, 4-nitro-3,5-dimethylpyrazole, 4-bromo-3,5-dimethylpyrazole, and 3-methyl-5-phenylpyrazole; imidazoles or imidazole derivatives such as imidazole, benzimidazole, 2-methylimidazole, 2-ethylimidazole, and 2-phenylimidazole; and imidazoline derivatives such as 2-methylimidazoline and 2-phenylimidazoline.

[0176] Examples of the ketone compound include methyl ethyl ketone and methyl isobutyl ketone.

[0177] Examples of commercially available blocked isocyanate compounds include the Duranate (blocked hexamethylene diisocyanate) series (manufactured by Asahi Kasei Corporation), Sumidur BL3175, Desmodur BL3272MPA, Desmodur BL3475 BA / SN, Desmodur BL3575 / 1 MPA / SN, Desmodur BL4265 SN, Desmodur BL5375 MPA / SN, and Desmodur VP LS2078 / 2 (all manufactured by Bayer).

[0178] The equivalent ratio (=OH / NCO) between the hydroxyl groups of the hydroxyl group-containing resin and the isocyanate groups of the polyisocyanate compound is not particularly limited. From the viewpoint of the curability and scratch resistance of the coating film, the equivalent ratio (=OH / NCO) is preferably 0.5 or more and 2.0 or less, and more preferably 0.8 or more and 1.5 or less.

[0179] (Third solvent) The clear coating (Z) contains a third solvent as needed. The third solvent is not particularly limited. The third solvent may be water, an organic solvent, or a combination thereof. Among them, water is preferred from the viewpoint of low VOC. The proportion of water in the third solvent is preferably 50% by mass or more, and more preferably 80% by mass or more. Examples of organic solvents used in the third solvent include the same organic solvents as those exemplified as the first solvent.

[0180] The amount of the third solvent is not particularly limited and is set appropriately depending on the solid content and viscosity of the clear coating (Z), etc. The third solvent is added, for example, so that the solid content of the clear coating (Z) is 30% by mass or more and 70% by mass or less.

[0181] (4) Curing process (S14) The uncured color coating film, the uncured bright coating film, and the uncured clear coating film are cured at the same time. Each coating film can be cured by heating.

[0182] Heating conditions are appropriately set depending on the composition of each coating film, etc. The heating temperature is, for example, 70°C to 150°C, and may be 80°C to 140°C. The heating time is, for example, 10 minutes to 40 minutes, and may be 20 minutes to 30 minutes. Examples of heating devices include drying ovens such as hot air ovens, electric ovens, and infrared induction heating ovens.

[0183] The present invention will be described in more detail below with reference to examples and comparative examples. However, the present invention is not limited to these examples. Note that "parts" and "%" are all based on mass.

[0184] [evaluation] (1) Lightness L * 45, CL * 45 Using a variable angle color difference meter (Gonio-Spectrophotometer GSP-1, manufactured by Murakami Color Materials Research Institute Co., Ltd.), light I was irradiated at a 45-degree angle onto the coating film. 45 The spectral reflectance was measured by receiving light at an angle of 45 degrees relative to the specular reflection. * a * b * Lightness L in the color system * 45 or CL * The average value of five different samples was used to calculate the lightness L * 45 or CL * I set it at 45.

[0185] (2)L * 5 / L * 15 Using a variable angle color difference meter (Gonio-Spectrophotometer GSP-1, manufactured by Murakami Color Materials Research Institute Co., Ltd.), light I was irradiated at a 45-degree angle onto the coating film. 45 The spectral reflectance was measured at angles of 5 degrees and 15 degrees relative to the specular reflection. * a * b * Lightness L in the color system * 5 and lightness L * The average value of five different samples was used to calculate the lightness L* 5 and lightness L * 15. Lightness L * 5 to Lightness L * Divide by 15 and get L * 5 / L * I asked for 15.

[0186] (3) Particle feeling G A multi-angle colorimeter (BYK-mac i, manufactured by BYK-Gardner) was used to measure the graininess G. The average value of five different samples was taken as the graininess G.

[0187] (4) Thickness of the glossy coating The thickness of the glitter coating was measured using an electromagnetic coating thickness meter (FISCHERSCOPE® MMS PC2, manufactured by Fischer Instruments Inc.) and the average value of five different samples was used as the thickness of the glitter coating.

[0188] (5) Occupancy rate The multilayer coating film was photographed from its normal direction using an industrial microscope (NICON, ECLIPSE LV150N), and the area corresponding to the luster material and other areas were binarized using image processing software. The area of ​​the observation field was set to 100%, and the area ratio of the luster material was calculated. The magnification for imaging was 200x. The observation field was 480nm vertically and 720nm horizontally. The average value of five different observation fields was taken as the occupancy rate.

[0189] (6)Si 15 value Using a multi-angle colorimeter (BYK-mac i, manufactured by BYK-Gardner), light was irradiated from a direction tilted 15 degrees from the normal direction of the multi-layer coating film, and the image was captured from the normal direction of the multi-layer coating film and analyzed to determine the Si 15 The average value of five different samples was calculated as Si 15 The value was set as

[0190] (7) Orientation of scale-like glittering material The cross section of the multilayer coating film was photographed using an industrial microscope (NICON, ECLIPSE LV150N). The angle θ between the surface of the glittering coating film and the scale-like glittering material within the observation field was calculated using the above method. When the angle θ was 30 degrees or less, it was determined that the surface of the glittering coating film and the scale-like glittering material were parallel.

[0191] (8) Placement of luminous materials The cross section of the multi-layer coating film was photographed using an industrial microscope (NICON Corporation, ECLIPSE LV150N). The number of overlapping glitter particles within the observation field was calculated using the method described above.

[0192] [Example 1] (I) Preparation of the object to be coated A zinc phosphate-treated steel sheet with a cured electrodeposition coating was prepared as a substrate. The cured electrodeposition coating was formed by electrodeposition coating the zinc phosphate-treated steel sheet with "Powernics," a cationic electrodeposition coating composition manufactured by Nippon Paint Co., Ltd., to a dry film thickness of 20 μm, followed by heating at 160°C for 30 minutes.

[0193] (II) Paint preparation (II-1) Preparation of colored paint 130.5 parts of a white pigment dispersion paste prepared as follows were mixed with 73.9 parts of a hydroxyl-containing acrylic resin emulsion resin (30 parts by resin solids), 60 parts of a hydroxyl-containing polyester resin (30 parts by resin solids), 100 parts of a hydroxyl-containing polyurethane resin (manufactured by Nippon Paint Automotive Coatings Co., Ltd.) (20 parts by resin solids), and 22.2 parts of Cymel 327 (a melamine resin manufactured by Nippon Cytec Industries Co., Ltd.) as a first curing agent. 40 parts of ion-exchanged water was then added to the mixture and further mixed. Next, 3.3 parts of Viscarex HV-30 (a polycarboxylic acid-based viscosity modifier manufactured by BASF, nonvolatile content 30%) as a viscosity modifier were added to the mixture, and the mixture was further mixed and stirred to obtain colored paint (X-1).

[0194] (Production of white pigment dispersion paste) 4.5 parts of Disperbyk 190 (a nonionic / anionic dispersant manufactured by BYK-Chemie) as a dispersant, 0.5 parts of BYK-011 (a nonionic / anionic dispersant manufactured by BYK-Chemie) as an antifoaming agent, 22.9 parts of ion-exchanged water, and 72.1 parts of titanium dioxide were premixed, and then glass bead media was added in a paint conditioner and mixed at room temperature until the secondary particle diameter of the titanium dioxide was 5 μm or less, yielding a pigment dispersion paste.

[0195] (Production of hydroxyl-containing acrylic resin emulsion) A typical acrylic resin emulsion production reactor equipped with a stirrer, thermometer, dropping funnel, reflux condenser, and nitrogen inlet tube was charged with 445 parts of water and 5 parts of Newcol 293 (Nippon Nyukazai Co., Ltd.) and heated to 75°C while stirring. A monomer mixture containing 145 parts of methyl methacrylate, 50 parts of styrene, 220 parts of ethyl acrylate, 70 parts of 2-hydroxyethyl methacrylate, and 15 parts of methacrylic acid, 240 parts of water, and 30 parts of Newcol 293 (Nippon Nyukazai Co., Ltd.) was emulsified using a homogenizer to obtain a monomer pre-emulsion. The monomer pre-emulsion was added dropwise over 3 hours while stirring in the reactor. Concurrently with the addition of the monomer pre-emulsion, an aqueous solution containing 1 part of APS (ammonium persulfate) as a polymerization initiator dissolved in 50 parts of water was added dropwise evenly to the reactor until the addition of the monomer pre-emulsion was completed. After the dropwise addition of the monomer pre-emulsion was completed, the reaction was continued for another hour at 80° C. After the reaction mixture was cooled, an aqueous solution of 2 parts of dimethylaminoethanol in 20 parts of water was added to the reaction vessel to obtain a hydroxyl group-containing acrylic resin emulsion with a solid content of 40.6% by mass.

[0196] The solid content of the obtained hydroxyl group-containing acrylic resin emulsion was found to have an acid value of 20 mg KOH / g, a hydroxyl value of 60 mg KOH / g, and a glass transition temperature (Tg) of 30° C. The solid content was measured according to JIS K 5601-1-2, the heating residue measurement method.

[0197] (Production of Hydroxyl Group-Containing Polyester Resin) A reactor was charged with 25.6 parts isophthalic acid, 22.8 parts phthalic anhydride, 5.6 parts adipic acid, 19.3 parts trimethylolpropane, 26.7 parts neopentyl glycol, 17.5 parts ε-caprolactone, and 0.1 parts dibutyltin oxide, and the mixture was heated to 170°C while stirring. The reaction mixture was then heated to 220°C over 3 hours, and water generated by the condensation reaction was removed until the acid value reached 8. Next, 7.9 parts trimellitic anhydride was added to the reactor and reacted at 150°C for 1 hour to obtain a polyester resin with an acid value of 40. The polyester resin was then cooled to 100°C, after which 11.2 parts butyl cellosolve was added and stirred until homogeneous. The polyester resin was then cooled to 60°C, and then 98.8 parts ion-exchanged water and 5.9 parts dimethylethanolamine were added. This resulted in a hydroxyl-containing polyester resin with a solids content of 50% by mass. The solid content of the hydroxyl-containing polyester resin was found to have an acid value of 40 mgKOH / g, a hydroxyl value of 110 mgKOH / g, a number average molecular weight of 2870, and a glass transition temperature (Tg) of -3°C. The glass transition temperature (Tg) was measured using a differential scanning calorimeter (DSC220C) manufactured by Seiko Instruments Inc. (SII). The measurement conditions were a sample size of 10 mg, a temperature rise rate of 10°C / min, and a measurement temperature of -20°C to 100°C.

[0198] (II-2) Preparation of glitter pigment dispersion Deionized water was added to 1.05 parts of CAB, 0.16 parts of cellulose nanofibers, 0.16 parts of scaly aluminum particles A, 6.55 parts of aluminum-dissolving thinner, 0.51 parts of titanium dioxide, 1.49 parts of acrylic resin, 1.08 parts of thermosetting resin, 0.42 parts of phosphoric acid, 0.72 parts of amine, and 0.51 parts of antifoaming agent, so that the total amount was 100 parts, and the mixture was stirred to obtain a brilliant pigment dispersion (Y-1).

[0199] The scaly aluminum particles A used were those manufactured by Toyo Aluminum Co., Ltd. under the trade name "EMR-D4670" with a thickness of 0.16 μm and an average particle diameter of 8 μm. The solid content of the bright pigment dispersion (Y-1) was 5.5%.

[0200] (II-3) Preparation of clear paint As the clear paint (Z-1), PU Excel O-2100 (two-component clear paint, manufactured by Nippon Paint Co., Ltd.) was prepared.

[0201] (III) Formation process of uncured colored coating film A colored paint (X-1) was applied to the object using Metabell.

[0202] (IV) Process for forming uncured glossy coating film The luster pigment dispersion (Y-1) was applied onto the uncured colored coating film using Metabell.

[0203] (V) Process for forming uncured clear coating film A clear coating (Z-1) was applied onto the uncured glossy coating film using a Micro Microbell.

[0204] (VI) Curing process After the clear coating film formation step (V), the substrate was heated at 140°C for 20 minutes to obtain a coated object having a multi-layer coating film A1. In the multi-layer coating film A1, the thickness of the colored coating film was 30 μm, and the black-and-white hiding film thickness of the colored coating film was 60 μm. The thickness of the glitter coating film was 0.5 μm. The thickness of the clear coating film was 30 μm.

[0205] (VII) Evaluation The above evaluations were carried out on the multi-layer coating film A1. The results of evaluations (1) to (5) are shown in Table 1. Regarding evaluation (6), the Si content of the multi-layer coating film A1 was 15 The value was 3.3. Regarding the evaluation (7) of the multi-layer coating film A1, 80% or more of the scale-like luminous materials were aligned parallel to the surface of the luminous coating film. Regarding the evaluation (8) of the multi-layer coating film A1, 80% or more of the scale-like luminous materials were not overlapping with other scale-like luminous materials.

[0206] [Comparative Example 1] Except for using carbon black as the colored coating, a coated object provided with a multi-layer coating film B1 was obtained in the same manner as in Example 1, and evaluations (1) to (5) were carried out. The results are shown in Table 1.

[0207] Comparative Example 2 In the glittering coating film forming step (IV), the glittering pigment dispersion was applied so that the glittering coating film in the resulting multilayer coating film would have a thickness of 2 μm. Except for this, a coated object provided with a multilayer coating film B2 was obtained in the same manner as in Example 1, and evaluations (1) to (5) were carried out. The results are shown in Table 1.

[0208] Comparative Example 3 In the preparation of the brilliant pigment dispersion (II-2), except that mica (thickness 1 μm, average particle diameter 17 μm) was used instead of the scaly aluminum particles A, a coated object having a multi-layer coating film B3 was obtained in the same manner as in Example 1, and evaluations (1) to (5) were carried out. The results are shown in Table 1.

[0209] Comparative Example 4 A coated object having a multilayer coating film B4 was obtained in the same manner as in Example 1, except that in preparation of a brilliant pigment dispersion (II-2), scaly aluminum particles B (product name "6320N", manufactured by Toyo Aluminum Co., Ltd., thickness 0.5 μm, average particle diameter 15 μm) were used instead of scaly aluminum particles A, and evaluations (1) to (5) were carried out. The results are shown in Table 1.

[0210] Comparative Example 5 A coated object having a multi-layer coating film B5 was obtained in the same manner as in Example 1, except that in the preparation of the bright pigment dispersion (II-2), deionized water was added so that the solid content of the bright pigment dispersion became 12%, and evaluations (1) to (5) were carried out. The results are shown in Table 1.

[0211] Comparative Example 6 A coated object having a multi-layer coating film B6 was obtained in the same manner as in Example 1, except that 0.32 parts of scaly aluminum particles A were added in preparation of the brilliant pigment dispersion (II-2), and evaluations (1) to (5) were carried out. The results are shown in Table 1.

[0212] [Table 1]

[0213] [Example 2] A coated object provided with a multi-layer coating film A2 was obtained and evaluated in the same manner as in Example 1, except that the following colored coating material (X-2), luster pigment dispersion (Y-2), and clear coating material (Z-2) were used. The results of evaluations (1) to (5) are shown in Table 1. Regarding evaluation (6), the Si content of the multi-layer coating film A2 was 15 The value was 3.3. Regarding the evaluation (7) of the multi-layer coating film A2, 80% or more of the scale-like luminous materials were aligned parallel to the surface of the luminous coating film. Regarding the evaluation (8) of the multi-layer coating film A2, 80% or more of the scale-like luminous materials were not overlapping with other scale-like luminous materials.

[0214] In the multi-layer coating film A2, the thickness of the colored coating film was 30 μm, the black and white hiding film thickness of the colored coating film was 60 μm, the thickness of the glitter coating film was 0.5 μm, and the thickness of the clear coating film was 30 μm.

[0215] (II-1) Preparation of colored paint In a stainless steel beaker, 7.59 parts of an acrylic resin having an epoxy group prepared as follows, 13.81 parts of Dianal HR-2077 (manufactured by Mitsubishi Rayon Co., Ltd., acrylic resin), 15.45 parts of Dianal HR-2025 (manufactured by Mitsubishi Rayon Co., Ltd., acrylic resin), 3.89 parts of U-Van 20N60 (manufactured by Mitsui Cytec Co., Ltd., butylated melamine resin), 3.89 parts of U-Van 226 (manufactured by Mitsui Chemicals Co., Ltd., butylated melamine resin), 0.99 parts of Mycoat 506 (manufactured by Mitsui Cytec Co., Ltd., butylated melamine resin), 1.91 parts of Sumidur BL-3175 (manufactured by Sumika Bayer Urethane Co., Ltd., block type polyisocyanate), 2 parts of Duranate MF-K60X (manufactured by Asahi Kasei Chemicals Corporation, HDI block polyisocyanate), TINUVIN 384-2 (manufactured by BASF Japan, ultraviolet absorber) 0.49 parts, CHISORB 523 (manufactured by Double Bond Chemical Ind., Co., Ltd., light stabilizer) 0.49 parts, Disparlon 4200-10 (manufactured by Kusumoto Chemicals, anti-sagging and anti-settling agent, oxidized polyethylene) 0.49 parts, Disparlon 4200-20 (manufactured by Kusumoto Chemicals, anti-sagging and anti-settling agent, oxidized polyethylene) 0.02 parts, BYK-110 (manufactured by BYK Japan, pigment dispersant) 0.04 parts, BYK-182 (manufactured by BYK Japan, pigment dispersant) 0.16 parts, Florene 0.05 parts of AC-300 (Kyoeisha Chemical Co., Ltd., a mixture of alkyl vinyl ether polymer, alkyl acrylate polymer, and alkyl methacrylate polymer), 0.37 parts of di-2-ethylhexyl phosphoric acid, white pigment, and a solvent composed of toluene / S-100 / S-150 / ethyl ethoxypropionate (mass ratio: 62 / 3 / 1 / 3) were added, and the mixture was mixed and stirred using a disper to obtain a colored paint (X-2).

[0216] (Production of acrylic resin having epoxy groups) A separable flask equipped with a reflux condenser, dropping funnel, thermometer, and stirring blade was charged with 520 parts of Solvesso 100 (S-100) and 50 parts of butyl acetate, and the temperature was raised to 120°C under a nitrogen atmosphere. A monomer mixture solution consisting of 250 parts of styrene, 60 parts of n-butyl acrylate, 60 parts of isobutyl methacrylate, 173 parts of isobornyl acrylate, 103 parts of 2-hydroxyethyl acrylate, 354 parts of glycidyl methacrylate, 28.5 parts of Kayaester-O, and 50 parts of butyl acetate was added dropwise through the dropping funnel at a constant rate over 3 hours. After the addition was completed, the mixture was stirred for an additional 30 minutes while maintaining the nitrogen atmosphere and temperature. Subsequently, a mixture of 40 parts of butyl acetate and 99 parts of Kayaester-O was added dropwise through the dropping funnel at a constant rate over 30 minutes. After the addition was completed, the mixture was stirred for an additional 2 hours while maintaining the nitrogen atmosphere and temperature. Then, 20 parts of S-100 and 9 parts of butyl acetate were added to the flask to obtain an acrylic resin with a hydroxyl value of 50 mg KOH / g, an epoxy equivalent of 405 g / eq, and a number average molecular weight of 2150.

[0217] (II-2) Preparation of glitter pigment dispersion 0.41 parts of CAB, 0.8 parts of acrylic resin, 0.16 parts of thermosetting resin, 0.1 parts of blocked polyisocyanate, 0.1 parts of phosphoric acid, 0.5 parts of scaly aluminum particles A, 19.84 parts of aluminum dissolving thinner, 0.07 parts of surfactant, and a total of 77.77 parts of two types of dilution thinner were mixed and stirred to obtain a brilliant pigment dispersion (Y-2). The solids content of the brilliant pigment dispersion (Y-2) was 2.4%.

[0218] (II-3) Preparation of clear paint As the clear coating material (Z-2), Macflow O-1820 Clear (manufactured by Nippon Paint Co., Ltd., an acid-epoxy curing resin composition) was prepared.

[0219] Comparative Example 7 Except for using carbon black as the colored coating, a coated article provided with a multi-layer coating film B7 was obtained in the same manner as in Example 2, and evaluations (1) to (5) were carried out. The results are shown in Table 2.

[0220] [Comparative Example 8] In the glittering coating film forming step (IV), the glittering pigment dispersion was applied so that the glittering coating film in the resulting multilayer coating film would have a thickness of 2 μm. Except for this, a coated object having a multilayer coating film B8 was obtained in the same manner as in Example 2, and evaluations (1) to (5) were carried out. The results are shown in Table 2.

[0221] Comparative Example 9 A coated object having a multilayer coating film B9 was obtained in the same manner as in Example 2, except that in preparation of the brilliant pigment dispersion (II-2), mica (thickness 1 μm, average particle diameter 17 μm) was used instead of the scaly aluminum particles A, and evaluations (1) to (5) were carried out. The results are shown in Table 2.

[0222] [Comparative Example 10] A coated object having a multilayer coating film B10 was obtained in the same manner as in Example 2, except that in preparation of a brilliant pigment dispersion (II-2), scaly aluminum particles B (product name "6320N", manufactured by Toyo Aluminum Co., Ltd., thickness 0.5 μm, average particle diameter 15 μm) were used instead of scaly aluminum particles A, and evaluations (1) to (5) were carried out. The results are shown in Table 2.

[0223] [Comparative Example 11] In the preparation of the bright pigment dispersion (II-2), a diluting thinner was added so that the solid content of the bright pigment dispersion became 12%, and a coated object having a multi-layer coating film B11 was obtained in the same manner as in Example 2, and evaluations (1) to (5) were carried out. The results are shown in Table 2.

[0224] [Comparative Example 12] A coated object having a multilayer coating film B12 was obtained in the same manner as in Example 2, except that 1.0 part of scaly aluminum particles A was added in preparation of the brilliant pigment dispersion (II-2), and evaluations (1) to (5) were carried out. The results are shown in Table 2.

[0225] [Table 2] [Industrial Applicability]

[0226] The automobile body and the method of manufacturing an automobile body of the present invention are particularly applicable to the outer panels of an automobile body. [Explanation of symbols]

[0227] 100 Automobile bodies 10 Object to be coated 20 Multi-layer coating 21 Colored coating film 22 Bright coating film 221 Bright material 23 Clear coating

Claims

1. An automobile body having a coating object and a multi-layer coating film, The multi-layer coating film is A colored coating film formed on the substrate and containing a white pigment; A glittering coating film formed on the colored coating film and containing a glittering material; A clear coating film formed on the glossy coating film, Light I was irradiated at an angle of 45 degrees onto the surface of the multilayer coating film. 45 The brightness L based on the spectral reflectance of light received at an angle of 45 degrees to the regular reflected light * 45 is between 70 and 90, The light I 45 The brightness L based on the spectral reflectance of light received at an angle of 5 degrees with respect to the regular reflection light * 5 and the light I 45 The brightness L based on the spectral reflectance of light received at an angle of 15 degrees to the regular reflected light * Ratio to 15: L * 5 / L * 15 is equal to or greater than 1.2 and equal to or less than 2.5, The occupancy rate of the glittering material as viewed from the surface of the multilayer coating film is 10% or more and 30% or less, An automobile body, wherein the graininess of the surface of the multi-layer paint film is 1.0 or more and 3.0 or less.

2. The surface of the colored coating is irradiated with light at an angle of 45 degrees. 45 The brightness CL based on the spectral reflectance of light received at an angle of 45 degrees to the regular reflected light * 2. The automobile body of claim 1, wherein 45 is greater than or equal to 70 and less than or equal to 95.

3. 3. The automobile body according to claim 1, wherein the thickness of the glittering coating film is from 0.05 μm to 1.0 μm.

4. 3. The automobile body according to claim 1, wherein the luster material comprises a scale-like luster pigment having a thickness of 0.05 μm or more and 0.3 μm or less.

5. The automobile body according to claim 1 or 2, wherein the luster material comprises aluminum particles.

6. 3. The automobile body according to claim 1, wherein the glitter coating further comprises titanium dioxide.

7. A step of applying a colored coating material containing a white pigment onto an object to be coated to form an uncured colored coating film; A step of applying a glittering pigment dispersion containing a glittering material onto the uncured colored coating film to form an uncured glittering coating film; A step of applying a clear coating material onto the uncured glossy coating film to form an uncured clear coating film; and a step of curing the uncured color coating film, the uncured glitter coating film, and the uncured clear coating film to obtain a multi-layer coating film, Light I was irradiated at an angle of 45 degrees onto the surface of the multilayer coating film. 45 The brightness L based on the spectral reflectance of light received at an angle of 45 degrees to the regular reflected light * 45 is between 70 and 90, The light I 45 The brightness L based on the spectral reflectance of light received at an angle of 5 degrees with respect to the regular reflection light * 5 and the light I 45 The brightness L based on the spectral reflectance of light received at an angle of 15 degrees to the regular reflected light * Ratio to 15: L * 5 / L * 15 is equal to or greater than 1.2 and equal to or less than 2.5, The occupancy rate of the glittering material as viewed from the surface of the multilayer coating film is 10% or more and 30% or less, A method for manufacturing an automobile body, wherein the graininess of the surface of the multi-layer coating film is 1.0 or more and 3.0 or less.

8. 8. The method for manufacturing an automobile body according to claim 7, wherein the clear coating is a two-component coating containing a hydroxyl group-containing resin and a polyisocyanate compound.

9. The method for manufacturing an automobile body according to claim 7 or 8, wherein the solid content of the glittering pigment dispersion is from 0.1% by mass to 10.0% by mass.